Comparing Between Local and International Endorsement - Muchamad Teguh Prambudi (Politeknik Negeri Bandung, 2018)
Top athlete is turned into a part of the promotion to generate awareness and positive reaction to Ads. However, an Indonesia footballer has not been getting endorsed product or services. This research aims to explain how athlete endorsement can influence a purchase intention. With 381 respondents, this study used empirical test by Structure Equation Model (SEM) and Partial Least Square (PLS) for analyzing the relationship between variables. The first findings of this study indicate that both athlete endorsements has influence brand awareness, attitude to Ads and specifically impact on purchase intention. The second findings are the local athlete more influential than international athlete based on their impact on the three variables that used. This finding can be used for the company for selecting an endorsement in order to create an effective promotion.